A Case of a Large Seminal Vesicle Cyst Associated with Ipsilateral Renal Agenesis - Apostolos P. Labanaris; Vahudin Zugor; Bernd Meyer; Reinhold Nützel; Reinhard Kühn (The Scientific World Journal)
The diagnosis of seminal vesicle cysts is often delayed or missed as a result of both their rarity and wide spectrum of potentially confusing clinical and imaging findings they can produce. Although rare, they should be considered in men, especially with a history of renal agenesis, who exhibit o inexplicable irritable voiding symptoms, perineal discomfort or other genitourinary complaint of unclear etiology. We introduce such a case, and discuss its symptoms, radiological findings and its therapeutic approach.